Reliability of lower limb biomechanics in two sport-specific sidestep cutting tasks - Mok, K.-M.; Bahr, R.; Krosshaug, T. (Sports Biomechanics, 2018)
The purpose of this study was to assess the within- and between-session reliability of lower limb biomechanics in two sport-specific sidestep cutting tasks performed by elite female handball and football (soccer) athletes. Moreover, we aimed at determining the minimum number of trials necessary to obtain a reliable measure. Nineteen elite female handball and 22 elite female football (soccer) athletes (M ± SD: 22 ± 4 yrs old, 168 ± 5 cm, 66 ± 8 kg) were tested. The reliability was quantified by intra-class correlations (ICCs), typical error and Spearman`s rank correlation. Only minor improvements in ICC values were seen when increasing the number of trials from 3 to 5. Based on trials 1-3, all variables showed good to excellent within-session reliability (M ICC: 0.91, 95% CI: 0.89-0.93), fair to good between-session reliability (M ICC: 0.73, 95% CI: 0.70-0.76), moderately positive between-session rank correlation coefficients (M: 0.72, 95% CI: 0.69-0.76). A few frontal plane biomechanical variables displayed lower between-session reliability in the football task compared with the handball task. The moderately positive between-session ranking and practically small typical error implies that the measurements could reliably reproduce the ranking of individuals in multiple-session studies. Adequate reliability could be attained from 3 trials, with only minor improvements when adding more trials. ABSTRACT FROM AUTHOR